2022
DOI: 10.1039/d2nr01861f
|View full text |Cite
|
Sign up to set email alerts
|

Work function regulation of surface-engineered Ti2CT2MXenes for efficient electrochemical nitrogen reduction reaction

Abstract: Electrochemical converting nitrogen to ammonia is a promising way in modern agricultural and industrial fields, due to its suitable process and feasibility under a mild condition. Therefore, seeking electrocatalysts and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The rate-determining step Δ G of Cr 2 CO 2 with intralayer-antiferromagnetic character is lower than that of the other three Cr 2 CO 2 materials and is 0.18 eV. Compared with the rate-determining step Δ G of various other catalyst materials (Table 3), 47–49 that of Cr 2 CO 2 with intralayer-antiferromagnetic character is still the lowest, which indicates that Cr 2 CO 2 with intralayer-antiferromagnetic character shows excellent NRR catalytic activity.…”
Section: Resultsmentioning
confidence: 85%
“…The rate-determining step Δ G of Cr 2 CO 2 with intralayer-antiferromagnetic character is lower than that of the other three Cr 2 CO 2 materials and is 0.18 eV. Compared with the rate-determining step Δ G of various other catalyst materials (Table 3), 47–49 that of Cr 2 CO 2 with intralayer-antiferromagnetic character is still the lowest, which indicates that Cr 2 CO 2 with intralayer-antiferromagnetic character shows excellent NRR catalytic activity.…”
Section: Resultsmentioning
confidence: 85%
“…The work function theory for NRR predicts that a lowered work function results in smaller extra energy required to activate the N2 molecules on the catalyst surface, which enhances the FE for NRR [46]. This idea was further extrapolated by Zhang et al [47], where the authors reported that the regulation of work function resulting in better charge transfer efficiency of the material could further regulate the binding strength of the key intermediates of NRR. This concept is crucial according to the Sabatier principle that suggests that the binding of adsorbate and the subsequent intermediates on the catalyst surface should neither be too strong nor too weak so as to keep the steady state reaction going towards forward kinetics [48,49].…”
Section: Benefits and Consequences For Nrrmentioning
confidence: 98%
“…Therefore, nitrogen fertilizers are needed in agricultural production to promote plant growth and development. 31,182,183 However, with the widespread use of nitrogen fertilizers, waste disposal and other human activities, large amounts of nitrogen are released into the natural environment, causing "nitrogen pollution" and endangering human health and the natural environment. To address this issue, nitrogen cycle technology has emerged involving NRR, 11,31 Selective C-N coupling toward electrocatalytic urea synthesis 14,184 and nitrate electroreduction to ammonia (NO x RR).…”
Section: Nitrogen Cycle Technologymentioning
confidence: 99%